Role of oral misoprostol 600 mcg in active management of third stage of labour: a comparative study with carboprost 125 mcg, intramuscular - Ramappa, Rekha; Mohan, Hema; Gurusiddappa, Lepakshi B. (International Journal of Research in Medical Sciences, 2017)
Background: Objectives: To compare misoprostol 600 mcg, oral with carboprost 125 mcg, i.m., in the active management of third stage of labour. Methods: A total of 200 pregnant women of 38-42 weeks of gestation delivering vaginally in the Shivamogga institute of medical sciences, Shivamogga, Karnataka, India were selected for study. 100 women received misoprostol 600 mcg, orally and 100 women received carboprost 125 mcg, i.m. immediately after delivery of baby and cord clamping by the method of randomisation. Results: In the misoprostol group, mean blood loss is 134.9 ml, mean duration of the third stage of labour is 4.07 min and mean fall in hemoglobin is 0.34 g/dl. In the carboprost group, mean blood loss is 123.7 ml, mean duration of the third stage of labour is 3.73 min and mean fall in hemoglobin is 0.28 g/dl. There was no signiﬁcant difference between the two groups with regard to the above mentioned factors. There were 5 cases of PPH in the misoprostol group and 3 cases in the carboprost group. 21 cases in the misoprostol group and 14 cases in the carboprost group required additional oxytocics. Unpleasant side effects like diarrhoea and vomiting were more in carboprost group. Conclusion: Oral misoprostol is as effective as carboprost in AMTSL and can be used safely in vaginal deliveries for prevention of PPH, especially in non-institutional deliveries and in places of low resource settings.